Hubungan Antara Konformitas dan Agresivitas pada Remaja di SMA X Cirebon - Aziz Syamsul Nurudin; Purwadi; Yuzarion (Psyche 165 Journal, 2021)
This study aims to determine the relationship between conformity and aggressiveness. The research subjects used in this research are high school students in one of the schools in Cirebon, totaling 151 people. This study uses quantitative methods. The data collection technique consist of a conformity questionnaire to see the conformity the subject and an aggressiveness scale to measure the level of individual aggressiveness. The data analysis used is Pearson Product Moment Correlation. The results of data analysis showed a correlation coefficient of 0.347 with a significance of 0.000 (p <0.05) and showed that there was a very significant positive relationship between conformity and aggressiveness. The results of this study indicate that the contribution given by conformity to aggressiveness is 34.7% percent, this indicates a very significant relationship between the conformity variable and adolescent aggressiveness